Phagosome Escape of Rough Mycobacterium abscessus Strains in Murine Macrophage via Phagosomal Rupture Can Lead to Type I Interferon Production and Their Cell-To-Cell Spread - Kim, Bo-Ram; Kim, Byoung-Jun; Kook, Yoon-Hoh; Kim, Bum-Joon (Frontiers in Immunology, 2019)
Mycobacterium abscessus complex (MAB) is a rapidly growing mycobacterium (RGM) whose clinical significance as an emerging human pathogen has been increasing worldwide. It has two types of colony morphology, a smooth (S) type, producing high glycopeptidolipid (GPL) content, and a rough (R) type, which produces low levels of GPLs and is associated with increased virulence. However, the mechanism responsible for their difference in virulence is poorly known. By ultrastructural examination of murine macrophages infected, we found that MAB-R strains could replicate more actively in the macrophage phagosome than the S variants and that they could escape into cytosol via phagosomal rupture. The cytosolic access of MAB-R strains via phagosomal rupture led to enhanced Type I interferon (IFN) production and cell death, which resulted in their cell-to-cell spreading. This behavior can provide an additional niche for the survival of MAB-R strains. In addition, we found that their enhancement of cell death mediated cell spreading are dependent on Type I IFN signaling via comparison of wild-type and IFNAR1 knockout mice. In conclusion, our data indicated that a transition of MAB-S strains into MAB-R variants increased their virulence via enhanced Type I IFN production, which led to enhanced survival in infected macrophage via cell death mediated cell-to-cell spreading. This result provides not only a novel insight into the difference in virulence between MAB-R and -S variants but also hints to their treatment strategy.